Design and analysis of an adaptive board-to-board dynamic holographic interconnect. - O'Brien, D; Faulkner, G; Wilkinson, T; Robertson, B; Leyva, D (Optical Society of American (OSA), 2004)
We describe the design and analysis of an adaptive free-space optical interconnect between two circuit boards in a standard electronic backplane. An array of vertical-cavity surface-emitting lasers is used as the transmitter, and this communicates with a detector array on the receiver circuit board. Routing is achieved with a holographic crossbar that has a ferroelectric liquid-crystal spatial light modulator to display binary phase computer-generated holograms. A detailed analysis of a 48-channel interconnect designed to operate at 1 (Gbytes/s)/channel indicates that such a switch will operate successfully given typical components and card misalignments.